2020
DOI: 10.1016/j.japh.2020.02.018
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative study exploring opportunities for pharmacists to connect with young mental health consumers

Abstract: Author contributions: SM, FK, VS and AW participated in the design of the study. SM and VS conducted the interviews and SM transcribed 20 interviews. SM, VS and FK quality checked the interview transcripts. SM and FK facilitated the focus group using the nominal group technique. SM and HS analysed the data, which were discussed with the entire research team. SM and FK drafted the manuscript. All authors provided editorial comments, read and approved the final manuscript.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Pharmacists reported a lack of privacy when consulting with patients about their mental health. 77 , 84 , 102 Young mental health patients described a lack of privacy due to pharmacies’ open plan spaces 49 which was exacerbated during busy periods. 37 Studies from England and New Zealand showed many pharmacy users were unaware of the presence of a private consultation area, 54 , 55 especially young people 103 and because sometimes pharmacists did not offer the consultation room to their patients.…”
Section: Resultsmentioning
confidence: 99%
“…Pharmacists reported a lack of privacy when consulting with patients about their mental health. 77 , 84 , 102 Young mental health patients described a lack of privacy due to pharmacies’ open plan spaces 49 which was exacerbated during busy periods. 37 Studies from England and New Zealand showed many pharmacy users were unaware of the presence of a private consultation area, 54 , 55 especially young people 103 and because sometimes pharmacists did not offer the consultation room to their patients.…”
Section: Resultsmentioning
confidence: 99%
“…As the study was focused on other aspects of medication management, such as experiences obtaining medication from a community pharmacy, other data emerged that is reported elsewhere [40]. Following this period of concentrated data immersion, results were compared, anomalies resolved, and the dominant categories agreed upon by both researchers (SM, HS).…”
Section: Discussionmentioning
confidence: 99%
“…Data were managed using the software package NVivo© (version 12, QSR International Pty Ltd., Doncaster, Victoria, Australia) which enabled sophisticated filing, easy retrieval and complex interrogation across the dataset. Some of the minor themes and diverse cases identified in the analysis have been presented in the results; other themes are reported in another paper focused on pharmacy experiences [40].…”
Section: Discussionmentioning
confidence: 99%
“…When postsecondary students obtain prescription medication from pharmacies, there are opportunities for the team of pharmacy professionals to support them with their psychotropic medication use and promote mental health. Previous research provides insight into the need for pharmacists to move towards a better approach to connect with, and support, postsecondary students 39–41. However, there is a research gap in the exploration of relationships among postsecondary students’ state of mental health, psychotropic medication management knowledge/needs and pharmacy services.…”
Section: Introductionmentioning
confidence: 99%